Excited state properties of polycyclic hydrocarbons based dyes - Klysko, Yu.V.; Syrotyuk, S.V. (Condensed Matter Physics, 2019)
In this paper we present a comprehensive ab initio study of polycyclic hydrocarbons based dyes. The purpose of
the work is to obtain electronic properties of the materials which are supposed to be used in organic electronic
devices. The list of materials includes violanthrone (di-benzanthrone) derivatives which are already known as
industrial organic dyes. First, we have obtained ground-state properties by performing ab initio eigenvalue calculation within generalized gradient approximation (GGA). Then, Green’s function method has been used in
order to obtain excited state properties. The exciton eigenvalues, as well as imaginary part of dielectric function (DF) and density of states (DOS), have been evaluated from the Bethe-Salpeter equation (BS). The electronic
properties obtained here are in good agreement with available experimental data. В данiй роботi представлено вивчення пiгментiв на основi полiциклiчних ароматичних вуглеводнiв з
використанням ab initio методiв. Список дослiджених матерiалiв включає промисловi зеленi пiгменти,
похiднi бензантрону, якi є перспективними для використання в органiчнiй електронiцi. На першому етапi
власнi функцiї та власнi значення були отриманi з використанням узагальненого градiєнтного наближення (GGA). На другому етапi квазiчастинковi електроннi властивостi розрахованi в рамках наближення GW.
Енергiї екситонiв, уявна частина дiелектричної функцiї та густина станiв були одержанi з рiвняння БетеСолпiтера (BS). Отриманi електроннi властивостi добре зiставляються з наявними екпериментальними
даними.